2015
DOI: 10.1158/1078-0432.ccr-14-2854
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Heterogeneity Characterizes the Genetic Landscape of Pheochromocytoma and Defines Early Events in Tumorigenesis

Abstract: Purpose: Pheochromocytoma and paraganglioma (PPGL) patients display heterogeneity in the clinical presentation and underlying genetic cause. The degree of inter-and intratumor genetic heterogeneity has not yet been defined.Experimental Design: In PPGLs from 94 patients, we analyzed LOH, copy-number variations, and mutation status of SDHA, SDHB, SDHC, SDHD, SDHAF2, VHL, EPAS1, NF1, RET, TMEM127, MAX, and HRAS using high-density SNP array and targeted deep sequencing, respectively. Genetic heterogeneity was dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…vascular cells, immune cells and fibroblasts) in the tumour samples. We have previously shown that tumour cell purity differs between mutational subgroups36. This may contribute to the differences noted between different subgroups by the present study and others.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…vascular cells, immune cells and fibroblasts) in the tumour samples. We have previously shown that tumour cell purity differs between mutational subgroups36. This may contribute to the differences noted between different subgroups by the present study and others.…”
Section: Discussionsupporting
confidence: 61%
“…One patient with von Hippel-Lindau disease had bilateral disease with both tumours included in the cohort. The tumours had been previously studied for mutations in known driver genes and using high-density SNP array (data available for 35 of the tumours)3637. Tumour purity was estimated from SNP array data using ASCAT v. 2.138 as implemented in Nexus Copy-number Variation 7.5 (Biodiscovery Inc., CA).…”
Section: Methodsmentioning
confidence: 99%
“…Widespread genetic heterogeneity within these tumors as well as and between paired lesions has been recently shown (152). Of particular notice was the observed differences between paired primary and metastatic tumor lesions as well as indication of parallel evolution of different metastatic clones (152).…”
Section: Genetic Heterogeneity and Tumor Evolutionmentioning
confidence: 98%
“…As previously described, the estimation of tumor cellularity through light microscopy tended to overestimate the proportion of tumor cells. 20,21 This relatively low proportion of tumor cells is expected to reduce the sensitivity for somatic mutation detection and may explain the relatively low prevalence of TP53 mutations in high-grade tumors. Indeed, the tumor cell proportion was determined as less than 25% in 4/6 TP53 wt high-grade tumors.…”
Section: Discussionmentioning
confidence: 99%